Adjustment index pont for women and men (2014)
Arch of men and women is different, in men the dental arch is wide and in women of parabolic shape. There are indexes and methods for the prediction of the width and shape of the ideal arch in orthodontics; one of these indices is that of Pont whichdoes not take into account the differences between the sexes. Objectives: determine the effectiveness of the Pont index to employ men and women, adjust if necessary to the formulas of the Pont index to be able to apply to men and women. Materialsand methods: the research is descriptive, experimental and transverse. The sample was 139 study models, 94 models were of patients female and 45 of male patients, so 45 models of female patients at random were selected to match the samples. The actual values of the sample of men were compared using a Student's t with women and the result of analysis of Pont in men and women. Was carried out adjustment of the constants of the Pont index for women and men, we apply to both populations; the result was compared with the actual values interpremolar and intermolar in maxilla and mandible. Results: the analysis of Pont is not effective for use in men and women from Nayarit, there were differences between the two populations, the adjustments made for the female and male population was effective for use in the population of Nayarit. Conclusions: Pont index is not applicable because it overestimates the values of the male and female population of the population of Nayarit. The settings were effective and he is recommended to evaluate it for other populations.